1999
DOI: 10.1111/j.1530-0277.1999.tb04223.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Sleep in Alcohol Misusers and Dependent Alcoholics and the Impact Upon Outcome

Abstract: Self-reported sleep disturbance can provide clinicians with information to plan better treatment for alcohol misusers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 28 publications
8
56
0
5
Order By: Relevance
“…Consistent with other studies (8,(14)(15)(16), baseline insomnia predicted relapse to alcohol. Baseline insomnia remained a predictor of relapse even after controlling for severity of alcohol dependence and depressive symptoms.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with other studies (8,(14)(15)(16), baseline insomnia predicted relapse to alcohol. Baseline insomnia remained a predictor of relapse even after controlling for severity of alcohol dependence and depressive symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…Given that insomnia during early recovery has been linked to relapse (8,(14)(15)(16), the frequency and correlates of insomnia in alcoholics are important areas of investigation. The present study of patients with alcoholism investigated (a) the frequency and clinical correlates of insomnia, (b) the frequency of drinking to self-medicate insomnia, and (c) the relationships between insomnia, self-medication and subsequent relapse.…”
Section: Introductionmentioning
confidence: 99%
“…posttraumatic stress disorder; alcoholism; sleep; insomnia Sleep disturbances frequently co-occur with psychiatric disorders, including substance use disorders (SUDs) and posttraumatic stress disorder (PTSD) (Foster & Peters, 1999). Sleep symptoms typically reported among clinical populations include delayed sleep onset, poor sleep continuity, early morning awakening, and disturbed sleep architecture (Pressman & Orr, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A recent epidemiological study found that, in the general population, 11% of respondents reported using alcohol specifically to help them sleep (National Sleep Foundation, 2005). Alcohol consumption may initially lead to improved sleep latency, but it is ultimately associated with poorer sleep quality, early wakening, and insomnia (Crum et al, 2004;Foster & Peters, 1999). It remains unclear at this time whether chronic use of alcohol to induce sleep may result in the development of clinically significant abuse or dependence.…”
mentioning
confidence: 99%
“…Disordered sleep is thought to contribute to daytime fatigue and sleepiness in alcoholics, and has been found to predict those recovering alcoholics who are at greatest risk to relapse (Gillin et al 1994;Brower et al 1998;Drummond et al 1998;Foster et al 1999). The mechanisms that account for abnormal sleep in recovering alcoholics are poorly understood.…”
Section: Introductionmentioning
confidence: 99%